Supercurrent Induced by Chiral Coupling in Multiferroic/Superconductor Nanostructures - Bjoern Niedzielski; Chenglong Jia; Jamal Berakdar (Nanomaterials, 2021)
We study the transport and the superconducting dynamics in a layer of type II superconductor (SC) with a normal top layer that hosts a helical magnetic ordering that gives rise to spin-current-driven ferroelectric polarization. Proximity effects akin to this heterostructure result in an anisotropic supercurrent transport and modify the dynamic properties of vortices in the SC. The vortices can be acted upon and controlled by electric gating or other means that couple to the spin ordering in the top layer, which, in turn, alter the superconducting/helical magnet coupling characteristics. We demonstrate, using the time dependent Ginzburg–Landau approach, how the spin helicity of the top layer can be utilized for pinning and guiding the vortices in the superconducting layer.